Accumulation of Azole Drugs in the Fungal Plant Pathogen Magnaporthe oryzae Is the Result of Facilitated Diffusion Influx - Esquivel, Brooke D.; White, Theodore C. (Frontiers in Microbiology, 2017)
Magnaporthe oryzae is an agricultural mold that causes disease in rice, resulting in devastating crop losses. Since rice is a world-wide staple food crop, infection by M. oryzae poses a serious global food security threat. Fungicides, including azole antifungals, are used to prevent and combat M. oryzae plant infections. The target of azoles is CYP51, an enzyme localized on the endoplasmic reticulum (ER) and required for fungal ergosterol biosynthesis. However, many basic drug-pathogen interactions, such as how the azole gets past the fungal cell wall and plasma membrane, and is transported to the ER, are not understood. In addition, reduced intracellular accumulation of antifungals has consistently been observed as a drug resistance mechanism in many fungal species. Studying the basic biology of drug-pathogen interactions may elucidate uncharacterized mechanisms of drug resistance and susceptibility in M. oryzae and potentially other related fungal pathogens. We characterized intracellular accumulation of azole drugs in M. oryzae using a radioactively labeled fluconazole uptake assay to gain insight on whether azoles enter the cell by passive diffusion, active transport, or facilitated diffusion. We show that azole accumulation is not ATP-dependent, nor does it rely on a pH-dependent process. Instead there is evidence for azole drug uptake in M. oryzae by a facilitated diffusion mechanism. The uptake system is specific for azole or azole-like compounds and can be modulated depending on cell phase and growth media. In addition, we found that co-treatment of M. oryzae with ‘repurposed’ clorgyline and radio-labeled fluconazole prevented energy-dependent efflux of fluconazole, resulting in an increased intracellular concentration of fluconazole in the fungal cell.